Family Communication and Financial Literacy to Prevent Children's Consumptive Behavior in the Midst of Online Shopping and Paylater Trends - Aira Cecilia; M. Fikri Akbar; Sandy Allifiansyah (Universitas Ibn Khaldun, 2025)
The digitalization era has made Indonesian consumption patterns changed, especially with the trend of online shopping and the growth of paylater services, which growed 17 times in the last five years. This study aims to examine the role of family communication and financial literacy in reducing children’s consumptive behavior in the context of online shopping and paylater use. The method used is a literature review with a descriptive qualitative approach based on Consumer Socialization Theory. The findings show that family communication are important to prevent overspending through control, education, and guidance, which helps children develop responsible spending habits. Open discussions and strong emotional connections between parents and children are important in in this case. Other solutions such as early financial education, learning how to budget, save, and set shopping priorities, can reduce impulsive buying behavior. The challenges of the digital era, with easy access to e-commerce and paylater that increase impulsive buying risks, making it a must to have strategies such as gadget use supervision, practical education about financial technology risks, and parental role modeling. The study concludes that a comprehensive approach combining effective family communication, sufficient financial literacy, and adaptive strategies is essential to prevent consumptive behavior among Indonesian youth